2020
DOI: 10.3390/ijerph17228554
|View full text |Cite
|
Sign up to set email alerts
|

Repercussion of COVID-19 Pandemic on Brazilians’ Quality of Life: A Nationwide Cross-Sectional Study

Abstract: The COVID-19 outbreak, caused by Sars-Cov-2, was officially declared a global pandemic in February 2020, after an unexpected increase in hospitalization and mortality. When faced with this new disease, social and physical distancing and quarantine emerged as solutions to reduce virus transmission. This article examines the quality of life (QoL) of the Brazilian population’s during this period of isolation, due to the COVID-19 pandemic by analyzing; physical, psychological, social, and economic aspects. An onli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
4
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 26 publications
(30 reference statements)
3
23
4
6
Order By: Relevance
“…Further, 7.9% ( n = 11) CD individuals reported a relative presenting respiratory symptoms suggestive of Sard-CoV-2 infection [ 20 ]. Our findings were worse compared to the study with the general Brazilian population [ 26 ] in which 2.7% of the participants had COVID-19 and 16% ( n = 300) of the participants had a relative who presented Sars-Cov-2 infection. Considering that the Brazilian study with the general population ended data collection (14 August 2020) 14 days before our study (28 August 2020) and the number of cases and deaths were continuously increasing, it is not possible to affirm that the incidence of COVID-19 was higher in CD individuals or their relatives than the general population in Brazil.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Further, 7.9% ( n = 11) CD individuals reported a relative presenting respiratory symptoms suggestive of Sard-CoV-2 infection [ 20 ]. Our findings were worse compared to the study with the general Brazilian population [ 26 ] in which 2.7% of the participants had COVID-19 and 16% ( n = 300) of the participants had a relative who presented Sars-Cov-2 infection. Considering that the Brazilian study with the general population ended data collection (14 August 2020) 14 days before our study (28 August 2020) and the number of cases and deaths were continuously increasing, it is not possible to affirm that the incidence of COVID-19 was higher in CD individuals or their relatives than the general population in Brazil.…”
Section: Discussioncontrasting
confidence: 99%
“…Different from the study that was performed with the general Brazilian population ( n = 1877) during the pandemic in which gender differed for all QoL domains (males with better QoL than females) [ 26 ], no significant difference was found for the CDQ during the pandemic regarding gender. Our result was also different from the Brazilian CD individuals’ QoL study performed before the pandemic in which males’ scores for the CDQ were higher than females, except for the “gastrointestinal” domain.…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“… 3 ; 4 ; 5 ; 6 ; 7 ; 8 ; 9 ; 10 ; 11 ; 12 ; 13 ; 14 ; 15 ; 16 ; 17 ; 18 ; 20 ; 21 ; 22 ; 23 ; 24 ; 25 ; 26 ; 27 ; 28 .…”
Section: Uncited Referencesunclassified
“…Yet despite the great effort has been made a range of aspects associated with the presence of COVID-19, existing studies in socio-economic disciplines have not provided sufficient empirical evidences to understand how such an external shock can affect the quality of life. Even though several studies, to a certain degree, have showed that people are more likely to be affect by socio and economic aspects than psychological and physical ones during this pandemic [ 25 ], attention was mainly focused on the perspective of people’s mental well-being [ 26 ] and specific aspects of their shopping behaviors [ 27 ]. Thus, there is a need to develop a theoretical framework that can deepen understanding of the multifaceted phenomenon of the socio-economic cost of public health policies concerning COVID-19.…”
Section: Introductionmentioning
confidence: 99%